2008
DOI: 10.3200/jach.56.44.395-400
|View full text |Cite
|
Sign up to set email alerts
|

College Health Professionals and Academic Librarians: Collaboration for Student Health

Abstract: The authors offer recommendations for partnerships between college healthcare professionals and academic librarians to better provide this information to students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…It is also important to realize that ''the relevant literature is not compiled in one place'' 8(p.1) and multiple sources need to be searched to conduct a thorough search. This further supports the submission [11][12][13] that doctors, nurses, and other health care professionals in teaching hospitals need support in the area of literature searching. Besides unfamiliarity with in-depth searching and the complexities of databases, health care professionals are busy providing health care and do not have the time or expertise to develop search strategies.…”
Section: Introductionsupporting
confidence: 73%
“…It is also important to realize that ''the relevant literature is not compiled in one place'' 8(p.1) and multiple sources need to be searched to conduct a thorough search. This further supports the submission [11][12][13] that doctors, nurses, and other health care professionals in teaching hospitals need support in the area of literature searching. Besides unfamiliarity with in-depth searching and the complexities of databases, health care professionals are busy providing health care and do not have the time or expertise to develop search strategies.…”
Section: Introductionsupporting
confidence: 73%
“…For college students, they are at a crucial stage of development and beginning to make lifelong health care decisions, and hence it is critical for them to develop proficient health literacy skills (Vogelpohl and Carpenter, 2013). Hallyburton, Kolenbrander and Robertson did a study on The University of North Carolina (UNC) and pointed out that librarians need to play a major role in helping students seek quality health information, while nearly three-quarters of academic library respondents in the UNC have not played an active role in offering health information, over 90% nevertheless felt it was their place to do so (Hallyburton et al, 2008). Ya-jun compared the situation of health information service in college and university library for students both in America and China and pointed out that it is necessary for college and university library carrying out health information service and also proposed the health information service strategies like popularizing health knowledge, enhancing collection construction, utilizing network new technology and improving the quality of librarians (Yajun, 2014).…”
Section: Literature Review 21 Health Information Service Of Academic Librariesmentioning
confidence: 99%
“…This organisation most recently set national goals for healthier American college students by 2020 (ACHA, 2021b ). Past ACHA‐NCHA reports have indicated that students demonstrate a need for reliable health information resources (Duhon & Jameson, 2013 ; Hallyburton et al, 2008 ). Up through 2009, the survey regularly asked students about their sources of health information (Vader et al, 2011 ).…”
Section: National Guidancementioning
confidence: 99%